HUBUNGAN ANTARA UMUR, PENGETAHUAN DAN KONSUMSI TABLET FE DENGAN KEJADIAN ANEMIA DI WILAYAH KERJA PUSKESMAS KUTALIMBARU TAHUN 2024 - Nainggolan, Anna Waris; Purba, Edy Marjuang; Lusiatun, Lusiatun (Universitas Negeri Medan, 2024)
The results of the 2023 Indonesian Health Survey show that the prevalence of anemia in pregnant women nationally has decreased by 21.2% (from 48.9% to 27.7%) but the decrease has not been evenly distributed in all regions. The prevalence of anemia is thought to be closely related to the mother's age at the time of pregnancy, the mother's knowledge regarding anemia and its prevention and non-compliant behavior in consuming Fe tablets. This study aims to determine the relationship between age, knowledge and consumption of Fe tablets with the incidence of anemia in the Kutalimbaru Health Center Work Area in 2024. This research is an analytical observational study using a cross sectional design. The sample was 52 pregnant women who lived in the Kutalimbaru Health Center Work Area who were taken using a purposive sampling technique. Primary data was obtained by conducting interviews with respondents and measuring the Hb of pregnant women. Data analysis was carried out using the Chi-square test with α=0.05. The proportion of mothers who experience anemia in the Kutalimbaru Community Health Center working area is 42.3%. There is a relationship between knowledge (p=0.039) and compliance with the consumption of Fe tablets (p=0.001) with the incidence of anemia in the Kutalimbaru Health Center Working Area. There is no relationship between age and the incidence of anemia in pregnant women. It is recommended that pregnant women, especially those in the Kutalimbaru Community Health Center work area, be proactive in seeking information and increasing their knowledge about anemia and how to prevent it. It is recommended that health workers supervise pregnant women in consuming Fe tablets.Keywords : Anemia, pregnant women, knowledge, consumption of Fe tablets